1989
DOI: 10.1029/ja094ia01p00121
|View full text |Cite
|
Sign up to set email alerts
|

Correlation studies between solar wind parameters and the decimetric radio emission from Jupiter

Abstract: Results of a study comparing long‐term time variations (years) in Jupiter's synchrotron radio emission with a variety of solar wind parameters and the 10.7‐cm solar flux are reported. Data from 1963 through 1985 were analyzed, and the results suggest that many solar wind parameters are correlated with the intensity of the synchrotron emission produced by the relativistic electrons in the Jovian Van Allen radiation belts. Significant nonzero correlation coefficients appear to be associated with solar wind ion d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 15 publications
2
44
0
2
Order By: Relevance
“…The observation of changes in the emission from Jupiter's electron belt has been reported since the early 1970s (e.g., Gérard 1970; Klein et al 1972Klein et al , 1989. Correlations with solar wind on timescales of months to years (e.g., Bolton et al 1989;Galopeau & Gérard 2001;Santos-Costa et al 2008) and solar radio flux on timescales of days to a week (e.g., Miyoshi et al 1999;Tsuchiya et al 2011;Kita et al 2013) have been confirmed since the 1990s. However, the response of the electron belt to the solar wind on short timescales has never been considered until the present work.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The observation of changes in the emission from Jupiter's electron belt has been reported since the early 1970s (e.g., Gérard 1970; Klein et al 1972Klein et al , 1989. Correlations with solar wind on timescales of months to years (e.g., Bolton et al 1989;Galopeau & Gérard 2001;Santos-Costa et al 2008) and solar radio flux on timescales of days to a week (e.g., Miyoshi et al 1999;Tsuchiya et al 2011;Kita et al 2013) have been confirmed since the 1990s. However, the response of the electron belt to the solar wind on short timescales has never been considered until the present work.…”
Section: Discussionmentioning
confidence: 84%
“…Changes in the spatial distribution of the electron belt are supposedly driven by either internal or external parameters (e.g., Bolton et al 1989;Brecht et al 2001;de Pater and Brecht 2001;Horne et al 2008;Santos-Costa et al 2008, 2011Kita et al 2013, and references therein). Determining the exact cause(s) of changes in the radio maps in Fig.…”
Section: Data Analysis Results From Rotation-averaged Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] It is well known that Jupiter is a source of synchrotron radiation whose strength seems to be related to solar activity [Bolton et al, 1989;Galopeau and Gerard, 2001]. Bolton et al suggested that solar activity may possibly modulate Jovian radiation belt electrons and found that the best correlation between solar wind parameters and the Jovian synchrotron radiation required a two year lag time most of which is presumably the response time of the Jovian magnetosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The inward flux of charged particles conserves the first two adiabatic invariants of motion while violating the third (Chang & Davis 1962). The particle source is believed to be the solar wind, and there is some evidence that the decimetric emission waxes and wanes with solar wind variations with approximately a 2 year lag (Bolton et al 1989). This synchrotron flux is extremely intense, permitting relatively easy detection of the emission from Earth and the generation of radio maps of the planet that manifest clear asymmetries in the planet's global magnetic field (e.g., de Pater 1981).…”
Section: Introductionmentioning
confidence: 99%